Dampak pH Terhadap Laju Korosi pada Aplikasi Electrical Assisted Oil Recovery (EAOR) - Anthony Jaya (Jurnal Nasional Pengelolaan Energi MigasZoom, 2021)
Corrosion is a common problem that occured in oil and gas field. In operating the well, the possibilities for pH changes is very high that could give a very dangerous impact to the corrosion. In the conventional well, pH will give an impact to the corrosion rate in a specific trend. As one of the new method in enhancing the oil production, Electrical Assisted Oil Recovery (EAOR) could give a promising result. However, the existence of electricity in this method could worsen the corrosion condition in a well. Therefore, this paper will make a research to determine the impact of pH in an EAOR well. This study is supported by a case study on oil field that use EAOR method in Indonesia. The case is having 8 pair wells which contains of 8 cathodes and 5 anodes. To observe the effect of pH, a sensitivity analysis is conducted with pH values ranging between 6.5 – 8.0. The result shows that there also an impact from pH to the corrosion rate in EAOR well but it shows a different pattern.